Sex Differences in Older Adults' Immune Responses to Seasonal Influenza Vaccination - Voigt, Emily A.; Ovsyannikova, Inna G.; Kennedy, Richard B.; Grill, Diane E.; Goergen, Krista M.; Schaid, Daniel J.; Poland, Gregory A. (Frontiers in Immunology, 2019)
Background: Sex differences in immune responses to influenza vaccine may impact efficacy across populations. Methods: In a cohort of 138 older adults (50–74 years old), we measured influenza A/H1N1 antibody titers, B-cell ELISPOT response, PBMC transcriptomics, and PBMC cell compositions at 0, 3, and 28 days post-immunization with the 2010/11 seasonal inactivated influenza vaccine. Results: We identified higher B-cell ELISPOT responses in females than males. Potential mechanisms for sex effects were identified in four gene clusters related to T, NK, and B cells. Mediation analysis indicated that sex-dependent expression in T and NK cell genes can be partially attributed to higher CD4+ T cell and lower NK cell fractions in females. We identified strong sex effects in 135 B cell genes whose expression correlates with ELISPOT measures, and found that cell subset differences did not explain the effect of sex on these genes’ expression. Post-vaccination expression of these genes, however, mediated 41% of the sex effect on ELISPOT responses. Conclusions: These results improve our understanding of sexual dimorphism in immunity and influenza vaccine response.